Catalytic deoxygenation of palm oil over metal phosphides supported on palm fiber waste derived activated biochar for producing green diesel fuel. Issue 40 (13th September 2022) - Kaewtrakulchai, Napat; Fuji, Masayoshi; Eiad-Ua, Apiluck
Abstract : Palm oil deoxygenation over palm fiber activated biochar supported metal phosphide catalysts. Abstract : Palm oil conversion into green diesel by catalytic deoxygenation (DO) is one of the distinctive research topics in biorefinery towards a bio-circular-green economic model to reduce the greenhouse gas emissions. In this study, palm fiber waste was explored as an alternative precursor for the preparation of activated biochar as a support material. A new series of nickel phosphide (Ni–P) and iron phosphide (Fe–P) catalysts supported on palm fiber activated biochar (PFAC) was synthesized by wetness impregnation, and extensive characterization was performed by several techniques to understand the characteristics of the supported metal phosphide catalysts prior to palm oil deoxygenation for producing of green diesel (C15 –C18 hydrocarbons). The PFAC support exhibited suitable physicochemical properties for catalyst preparation, such as high carbon content, and high porosity ( S BET of 1039.64 m 2 g −1 with V T of 0.572 cm 3 g −1 ). The high porosity of the catalyst support (PFAC) significantly promotes the metal phosphide nanoparticle dispersion. The DO of palm oil was tested in a trickle bed down flow reactor under hydrogen atmosphere. The outstanding catalytic performance of supported Ni–P and Fe–P catalysts provided an impressive liquid hydrocarbon yield between 63.37 and 79.65% with the highest green diesel selectivity of 62.64%. Decarbonylation (DCO) and decarboxylation (DCO2 ) are the main pathways for the relative phosphide catalysts as presented by the high number of C n −1 atoms (C15 and C17 hydrocarbons). In addition, metal phosphide/PFAC catalysts could achieve great potential application as a promising alternative catalyst for biofuel production via deoxygenation for large-scale operation owing to their excellent catalytic activity, simple preparation, and utilization of sustainable resources.